Sodium-ion battery positive electrode chemical sodium pre-treatment reagent and method and sodium-ion battery
The problem of initial Coulombic efficiency of sodium ion battery oxide material is solved by pre-sodiumizing the positive electrode of sodium ion battery by using ethylene glycol diethyl ether and 2,2'-bipyridine and sodium metal configuration. , realizes efficient pre-sodiumization of the positive electrode material of sodium ion battery, and improves the circulation performance and stability of the battery.
Patent Information
- Application Number
- CN202411354930.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The initial Coulombic efficiency and poor cycle stability of sodium ion battery oxide cathode materials are low, and the existing chemical pre-sodium reagents have extremely low redox potential and insufficient chemical stability, which limits their large-scale application.
Using chemical pre-sodium reagents arranged in diethyl ether and 2,2'-bipyridine and metal sodium, the positive electrode sheet is soaked in a pre-sodium solution in the drying room to control humidity and temperature. Improve redox potential and chemical stability.
It improves the first Coulomb efficiency and circulation performance of the positive electrode of sodium ion battery, is simple to operate, short process and high safety, is suitable for industrial applications, and the pre-sodiumization process can be carried out at room temperature.
Smart Images

Figure CN119252866A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion battery positive electrode chemical pre-sodiumization reagent and method and a sodium ion battery. Background Art
[0002] With the rapid growth of energy storage market demand, sodium-ion batteries are regarded as a promising emerging energy storage technology due to their abundant resources, low price and superior low-temperature performance. However, one of the main challenges facing sodium-ion batteries in commercial applications is the low initial sodium content of oxide cathode materials and their corresponding low initial Coulombic efficiency, which seriously affects the energy density and cycle stability of the whole battery. In order to overcome these problems, researchers have widely explored the pre-sodiumization strategy of oxide cathode materials in recent years. During the pre-sodiumization process, additional sodium ions are pre-introduced into the cathode to increase the initial sodium content of the material, thereby improving its initial Coulombic efficiency and cycle stability.
[0003] So far, the main pre-sodiumization strategies include sacrificial salt pre-sodiumization, electrochemical pre-sodiumization and chemical pre-sodiumization. Among them, the sacrificial salt pre-sodiumization method introduces sodium salts into the battery. After one charge and discharge cycle, these sodium salts will decompose and release sodium ions, thereby achieving pre-sodiumization. Electrochemical pre-sodiumization is to introduce sodium ions into the electrode material through an external electrochemical device before the battery is assembled. This method can accurately control the degree and uniformity of pre-sodiumization. The chemical pre-sodiumization method is based on the spontaneous reaction between the pre-sodium reagent and the electrode material to introduce sodium ions into the electrode material. Due to its simple operation, uniform reaction and controllable process, the chemical pre-sodiumization method has significant potential for scalable application. By selecting suitable chemical pre-sodiumization reagents and optimizing reaction conditions, efficient pre-sodiumization can be achieved, thereby improving the initial coulombic efficiency and cycle performance of sodium-ion batteries.
[0004] At present, the widely used chemical pre-sodium reagents are polycyclic aromatic hydrocarbons, such as naphthalene and biphenyl. These special organic compounds have conjugated large π bonds and can react with various alkali metals to form alkali metal-organic solutions with strong reducing properties. As pre-sodium reagents, they have been widely used in positive and negative electrode materials of sodium ion batteries. However, such pre-sodium reagents usually have extremely low redox potentials (about 0.1V vs. Na + / Na), which can easily cause excessive pre-sodiumization and structural damage of the cathode material. In addition, the pre-sodiumization process must be completed in a glove box atmosphere due to the poor chemical stability of the solvent, which seriously limits its large-scale application. Therefore, how to design a cathode pre-sodiumization reagent with controllable redox potential and chemical stability remains challenging. Summary of the invention
[0005] The purpose of the present invention is to solve the problem of low initial coulombic efficiency of oxide positive electrode materials for sodium ion batteries, and to provide a chemical pre-sodiumization reagent and method for the positive electrode of sodium ion batteries. The chemical pre-sodiumization reagent used in the present invention has the characteristics of suitable redox potential and good chemical stability, and can be applied to commercial sodium ion batteries.
[0006] Based on the above purpose, the technical solution of the present invention is as follows:
[0007] In the first aspect, the embodiment of the present invention provides a novel sodium ion battery positive electrode chemical pre-sodium reagent, wherein ethylene glycol diethyl ether and 2,2'-bipyridine and metallic sodium are used to prepare the chemical pre-sodium reagent; the concentration of the solute in the 2,2'-bipyridine sodium solution is 0.001 mol L -1 ~2mol L -1 .
[0008] In a second aspect, an embodiment of the present invention provides a chemical pre-sodium method in a non-glove box (drying room), wherein the pre-sodium solution described in any one of the first aspects is placed in a drying room environment, and several positive electrode sheets are soaked in the pre-sodium solution. After 1 to 10 minutes, the positive electrode sheets are taken out, washed and dried to obtain a pre-sodiumized sodium ion battery positive electrode.
[0009] Preferably, the drying room environment directly affects the stability of the pre-sodium solution, and humidity and moisture need to be strictly controlled. The dew point range of the drying room is -20°C to -40°C, and the temperature is usually controlled between 20°C and 30°C.
[0010] Preferably, the pre-sodium time is 5 min to 10 min.
[0011] In a third aspect, an embodiment of the present invention provides a sodium ion battery comprising the pre-sodium positive electrode sheet, wherein the pre-sodium positive electrode sheet, diaphragm, electrolyte and negative electrode sheet of the sodium ion battery are assembled in a glove box atmosphere to finally obtain a sodium ion battery; wherein the diaphragm is glass fiber; the solute in the electrolyte is 1M NaPF6, the solvent is diethylene glycol dimethyl ether, and the negative electrode sheet is a metallic sodium sheet or a hard carbon negative electrode.
[0012] Advantages and beneficial effects of the present invention:
[0013] The present invention uses 2,2'-bipyridyl sodium / ethylene glycol diethyl ether reagents with mild reaction and stable properties to pre-sodiumize the positive electrode material of the sodium ion battery. The method can be carried out in a room with normal temperature and drying, and has simple operation, short process flow, rapid reaction, high safety, and is very easy to industrialize. At the same time, the pre-sodiumized positive electrode can make up for the defect of insufficient sodium itself, and effectively improve the first coulomb efficiency of the positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 11 is a cyclic voltammetry test curve diagram of different solute (Na-Biph, Na-Bpy) pre-sodium solutions obtained in Example 1 and Comparative Example 1;
[0015] Figure 2 The first week charge-discharge curves of the initial and Na-Bpy / DEE solution pre-sodium 5 min oxide positive electrode materials obtained in Example 1;
[0016] Figure 3 The first week charge-discharge curves of the initial and Na-Bpy / DEE solution pre-sodium 10 min oxide positive electrode materials obtained in Example 2;
[0017] Figure 4 The first week charge and discharge curves of the initial and Na-Bpy / DME solution pre-sodium 5min oxide positive electrode materials obtained in Comparative Example 2;
[0018] Figure 5 The first week charge and discharge curves of the initial and Na-Bpy / DME solution pre-sodium 10 min oxide positive electrode materials obtained in Comparative Example 3 are shown;
[0019] Figure 6 The diagram is a diagram of the change of the pre-sodium solution obtained in Example 3 and Comparative Example 4 after standing for 1 hour in a drying room (the left side is Na-Bpy / DME solution, and the right side is Na-Bpy / DEE solution);
[0020] Figure 7 The first week charge and discharge curves of the sodium oxide positive electrode material obtained in the dry room initially and in the Na-Bpy / DEE solution pre-treatment were shown in Example 3;
[0021] Figure 8 The initial and Na-Bpy / DEE solution pre-sodium P2-Na obtained in Example 3 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 / / First cycle charge and discharge curve of hard carbon full battery;
[0022] Fig. 9 The initial and Na-Bpy / DEE solution pre-sodium P2-Na obtained in Example 3 2 / 3 Ni 1 / 3 Mn 2 / 3 Cycle diagram of O2 / / hard carbon full battery;
[0023] Fig.10 This is the charge and discharge curve of the first week of the sodium oxide positive electrode material obtained in the dry room initially and in the Na-Bpy / DME solution pre-prepared. DETAILED DESCRIPTION
[0024] The present invention is described in detail and completely below in conjunction with the accompanying drawings, but these embodiments are not intended to limit the scope of protection of the present invention. The reagents used in the examples are all purchased from the market or obtained by conventional synthesis methods in the art unless otherwise specified.
[0025] Example 1
[0026] In a glove box, 10 mL of ethylene glycol diethyl ether (DEE) solvent was added with 0.312 g of 2,2'-bipyridine (Bpy), and magnetic stirring was performed for 30 min to obtain a homogeneous clear solution. 0.046 g of metallic sodium was added to the obtained solution, and magnetic stirring was performed for 120 min to obtain a uniform dark purple solution with a concentration of 0.2 mol L -1 Chemical pre-sodium solution Na-Bpy / DEE. 2 / 3 Ni 1 / 3 Mn 2 / 3 The O2 positive electrode was placed in the pre-sodium solution for 5 min. After the reaction was complete, it was washed three times with DEE and dried at 60°C for 2 h.
[0027] The pre-sodiumized positive electrode sheet and the sodium sheet were assembled into a half-cell, with a positive electrode active material loading of 1.5 mg cm -2 , at 0.2mV s -1 Cyclic voltammetry tests were performed in the voltage range of 1.5V-4.15V at a scan rate. Figure 1 (Top) is the cyclic voltammetry test curve of the Na-Bpy / DEE pre-sodium solution used in Example 1, and its redox potentials are 0.33V and 0.40V respectively.
[0028] The pre-sodiumized positive electrode sheet and the sodium sheet were assembled into a half-cell, with a positive electrode active material loading of 1.5 mg cm -2 , at 50mA g -1 Under current density, constant current charge and discharge tests were carried out in the voltage range of 1.5V-4.15V. Figure 2 The initial and pre-sodium 5min P2-Na used in Example 1 2 / 3 Ni 1 / 3 Mn 2 / 3 The first cycle charge and discharge curve of the O2 electrode. Electrochemical tests show that the open circuit voltage of the half-cell decreases from 2.826V to 1.821V after pre-sodiumization. 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 86.4 mAh g -1 and 151.2mAh g -1 , and after pre-sodiumization, P2-Na 2 / 3 Ni 1 / 3 Mn2 / 3 The first charge and discharge capacities of the O2 positive electrode were 155.8 mAh g -1 and 153.0mAh g -1 , for the first time, the Coulomb efficiency was increased from 57.14% to 100%.
[0029] Comparative Example 1
[0030] In a glove box, 10 mL of ethylene glycol diethyl ether (DEE) solvent was added with 0.308 g of biphenyl (Biph), and magnetic stirring was performed for 30 min to obtain a homogeneous clear solution. 0.046 g of metallic sodium was added to the obtained solution, and magnetic stirring was performed for 120 min to obtain a uniform dark blue solution with a concentration of 0.2 mol L -1 Chemical pre-sodium solution Na-Biph / DEE. 2 / 3 Ni 1 / 3 Mn 2 / 3 The O2 positive electrode was placed in the pre-sodium solution for 5 min. After the reaction was complete, it was washed three times with DEE and dried at 60°C for 2 h.
[0031] The pre-sodiumized positive electrode sheet and the sodium sheet were assembled into a half-cell, with a positive electrode active material loading of 1.5 mg cm -2 , at 0.2mV s -1 Cyclic voltammetry tests were performed in the voltage range of 1.5V-4.15V at a scan rate. Figure 1 (Below) is the cyclic voltammetry test curve of the Na-Biph / DEE pre-sodium solution used in Comparative Example 1, and its redox potential is 0.16V and 0.20V respectively. Compared with the Na-Bpy / DEE pre-sodium solution of Example 1, the Na-Biph / DEE pre-sodium solution has a lower redox potential, which is easy to cause excessive pre-sodiumization and structural damage of the positive electrode material. Therefore, the sodium biphenyl pre-sodium solution is not suitable for pre-sodiumization of layered oxide positive electrode materials.
[0032] Example 2
[0033] The difference from Example 1 is that P2-Na 2 / 3 Ni 1 / 3 Mn 2 / 3 The O2 positive electrode was placed in the pre-sodium solution for 10 min.
[0034] The pre-sodiumized positive electrode sheet and the sodium sheet were assembled into a half-cell, with a positive electrode active material loading of 1.5 mg cm -2 , at 50mA g -1 Under current density, constant current charge and discharge tests were carried out in the voltage range of 1.5V-4.15V. Figure 3 The initial and pre-sodium 10min P2-Na used in Example 2 2 / 3 Ni1 / 3 Mn 2 / 3 The first cycle charge and discharge curve of the O2 electrode. Electrochemical tests show that the open circuit voltage of the half-cell decreases from 2.826V to 1.793V after pre-sodiumization. 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 86.4 mAh g -1 and 151.2mAh g -1 , and after pre-sodiumization, P2-Na 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 184.7 mAh g -1 and 155.5mAh g -1 As the pre-sodium treatment time increases, the first cycle charge capacity further increases, while the electrochemical curve platform of the cathode material remains consistent with that of the initial material, indicating that the Na-Bpy / DEE pre-sodium solution can maintain the structural stability of the cathode material during the long-term pre-sodium treatment process.
[0035] Comparative Example 2
[0036] The difference from Example 1 is that ethylene glycol diethyl ether (DEE) is replaced by ethylene glycol dimethyl ether (DME).
[0037] The pre-sodiumized positive electrode sheet and the sodium sheet were assembled into a half-cell, with a positive electrode active material loading of 1.5 mg cm -2 , at 50mA g -1 Under current density, constant current charge and discharge tests were carried out in the voltage range of 1.5V-4.15V. Figure 4 The initial and pre-sodium 5min P2-Na used in Comparative Example 2 2 / 3 Ni 1 / 3 Mn 2 / 3 The first cycle charge and discharge curve of the O2 electrode. Electrochemical tests show that the open circuit voltage of the half-cell decreases from 2.826V to 1.825V after pre-sodiumization. 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 86.4 mAh g -1 and 151.2mAh g -1 , and after pre-sodiumization, P2-Na 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 154.9 mAh g -1 and 152.5mAh g -1 , for the first time, the Coulombic efficiency was increased from 57.14% to 100%.
[0038] Comparative Example 3
[0039] The difference from Comparative Example 2 is that P2-Na 2 / 3 Ni 1 / 3 Mn 2 / 3 The O2 positive electrode was placed in the pre-sodium solution for 10 min.
[0040] The pre-sodiumized positive electrode sheet and the sodium sheet were assembled into a half-cell, with a positive electrode active material loading of 1.5 mg cm -2 , at 50mA g -1 Under current density, constant current charge and discharge tests were carried out in the voltage range of 1.5V-4.15V. Figure 5 The initial and pre-sodium 10min P2-Na used in Comparative Example 3 2 / 3 Ni 1 / 3 Mn 2 / 3 The first cycle charge and discharge curve of the O2 electrode. Electrochemical tests show that the open circuit voltage of the half-cell decreases from 2.826V to 1.761V after pre-sodiumization. 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 86.4 mAh g -1 and 151.2mAh g -1 , and after pre-sodiumization, P2-Na 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 186.9 mAh g -1 and 101.3mAh g -1 As the pre-sodium treatment time increases, the first cycle charge capacity further increases; however, compared with the initial material, the electrochemical curve platform of the cathode material becomes smooth and the discharge capacity is significantly reduced, indicating that the Na-Bpy / DME pre-sodium solution will destroy the structural stability of the cathode material during the long-term pre-sodium treatment process.
[0041] Example 3
[0042] The difference from Example 1 is that the glove box is replaced with a drying room.
[0043] Figure 6 (The bottle on the right) shows the changes of the Na-Bpy / DEE pre-sodium solution prepared in the drying room after standing for 1 hour. It is observed that the initial pre-sodium solution and the pre-sodium solution after standing for 1 hour are consistent and basically unchanged, indicating that the Na-Bpy / DEE pre-sodium solution has good chemical stability.
[0044] The positive electrode sheet pre-sodiumized in the drying room is assembled into a half-cell with a sodium sheet, and the positive electrode active material loading is ~1.5mgcm -2, at 50mAg -1 Under current density, constant current charge and discharge tests were carried out in the voltage range of 1.5V-4.15V. Figure 7 The initial and drying pre-sodium P2-Na used in Example 3 2 / 3 Ni 1 / 3 Mn 2 / 3 The first cycle charge and discharge curve of the O2 electrode. Electrochemical tests show that the open circuit voltage of the half-cell decreases from 2.826V to 1.833V after pre-sodiumization. 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 86.4 mAh g -1 and 151.2mAh g -1 , and after pre-sodiumization, P2-Na 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 155.1 mAh g -1 and 153.5mAh g -1 The first coulombic efficiency increased from 57.14% to 100%. The results show that Na-Bpy / DEE solution can achieve positive electrode pre-sodiumization in the drying room and can maintain good electrochemical performance.
[0045] The above-mentioned pre-sodium-treated positive electrode sheet is matched with the hard carbon negative electrode to assemble into a full battery, and the positive electrode active material loading is ~4mgcm -2 , at 200mA g -1 Under current density, constant current charge and discharge tests were carried out in the voltage range of 1.4V-4.05V. Figure 8 P2-Na for the initial and Na-Bpy / DEE solution after pre-sodiumization 2 / 3 Ni 1 / 3 Mn 2 / 3 The first cycle charge and discharge curve of O2 / / hard carbon full battery. Electrochemical tests show that the open circuit voltage of the half-cell decreases from 0.198V to -0.269V after pre-sodiumization. 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 / / hard carbon full battery are 89.4 mAh g -1 and 49.3mAh g -1 , and after pre-sodiumization, P2-Na 2 / 3 Ni 1 / 3Mn 2 / 3 The first charge and discharge capacities of the O2 / / hard carbon full battery are 179.9 mAh g -1 and 135.7mAh g -1The results show that the full battery after pre-sodium treatment exhibits higher capacity than the full battery without pre-sodium treatment. Fig. 9 After pre-sodiumization of Na-Bpy / DEE solution, P2-Na 2 / 3Ni 1 / 3 Mn 2 / 3 O2 / / Cycling performance of hard carbon full battery, capacity is 0.5Ah, and capacity retention rate is ~100% after 40 cycles.
[0046] Comparative Example 4
[0047] The difference from Comparative Example 2 is that the glove box is replaced with a drying room.
[0048] Figure 6 (Left bottle) shows the change of Na-Bpy / DME pre-sodium solution prepared in the drying room after standing for 1 hour. It is observed that the initial pre-sodium solution and the pre-sodium solution after standing for 1 hour are consistent and basically unchanged, indicating that the Na-Bpy / DME pre-sodium solution has good chemical stability.
[0049] The pre-sodiumized positive electrode sheet and the sodium sheet were assembled into a half-cell, with a positive electrode active material loading of 1.5 mg cm -2 , at 50mA g -1 Under current density, constant current charge and discharge tests were carried out in the voltage range of 1.5V-4.15V. Fig.10 The initial and drying pre-sodium P2-Na used in Comparative Example 4 2 / 3 Ni 1 / 3 Mn 2 / 3 The first cycle charge and discharge curve of the O2 electrode. Electrochemical tests show that the open circuit voltage of the half-cell decreases from 2.826V to 1.910V after pre-sodiumization. 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 86.4 mAh g -1 and 151.2mAh g -1 , and after pre-sodiumization, P2-Na 2 / 3 Ni 1 / 3 Mn 2 / 3 The first charge and discharge capacities of the O2 positive electrode were 139.67 mAh g -1 and 129.05mAh g -1 The results showed that Na-Bpy / DME solution can achieve pre-sodiumization of the positive electrode in the drying room, but its electrochemical curve was observed to be relatively smooth and the capacity decayed.
[0050] In summary, the method of pre-sodiumization of the positive electrode of sodium ion battery using 2,2'-bipyridyl sodium / ethylene glycol diethyl ether reagent has the best effect. The pre-sodium solution has a suitable redox potential and avoids destroying the structural stability of the oxide positive electrode material. At the same time, the pre-sodium process can be carried out in a room with room temperature and dryness, and has no effect on the subsequent electrochemical properties of the material. The P2-Na obtained by this method 2 / 3 Ni 1 / 3 Mn 2 / 3 O2 positive electrode materials have high first-cycle efficiency and stable cycle performance, and have broad research prospects and application value.
[0051] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A sodium ion battery positive electrode chemical pre-sodium reagent, characterized in that The chemical pre-sodium reagent was prepared with ethylene glycol diethyl ether, 2,2'-bipyridine and metallic sodium; the concentration of the solute in the 2,2'-bipyridine sodium solution was 0.001 mol L -1 ~2molL -1 .
2. A pre-sodiumization method for a pre-sodiumization reagent according to claim 1, characterized in that, The pre-sodiumization reagent is placed in a drying room environment, and the positive electrode sheet is soaked in the pre-sodiumization reagent. After 1 to 10 minutes, the positive electrode sheet is taken out, washed and dried to obtain a pre-sodiumized sodium ion battery positive electrode.
3. The method according to claim 2, characterized in that The dew point range of the drying room is -20°C to -40°C, and the temperature range of the drying room is 20°C to 30°C.
4. The method according to claim 2, characterized in that: The pre-sodium time is 5min to 10min.
5. A sodium ion battery, characterized in that: The invention comprises a pre-sodiumized sodium ion battery positive electrode, a separator, an electrolyte and a negative electrode sheet prepared by the method of any one of claims 2 to 4.
6. The sodium ion battery according to claim 5, characterized in that: The diaphragm is glass fiber, the solute in the electrolyte is 1M NaPF6, the solvent is diethylene glycol dimethyl ether; the negative electrode plate is a metal sodium plate or a hard carbon negative electrode.
Citation Information
Patent Citations
Electrolyte addictive as well as electrolyte with addictive and lithium ion battery
CN102324565A
Preliminary metal metallization method and its application in battery material
CN104766947A
Sodium ion battery negative electrode pre-sodium modification method, obtained negative electrode material and sodium ion battery
CN109546134A
Sodium ion battery negative electrode SEI film forming agent, sodium pre-modification method and sodium ion battery
CN112635709A
Chemical prealkaliation of electrodes
CN113039675A
Cited By
Conductive-bonding difunctional polymer binder, preparation method thereof and application of conductive-bonding difunctional polymer binder in sodium ion battery
CN121991606A